Computational drug discovery under RNA times. (14th November 2022) - Bernetti, Mattia; Aguti, Riccardo; Bosio, Stefano; Recanatini, Maurizio; Masetti, Matteo; Cavalli, Andrea
Abstract: Abstract: RNA molecules play many functional and regulatory roles in cells, and hence, have gained considerable traction in recent times as therapeutic interventions. Within drug discovery, structure-based approaches have successfully identified potent and selective small-molecule modulators of pharmaceutically relevant protein targets. Here, we embrace the perspective of computational chemists who use these traditional approaches, and we discuss the challenges of extending these methods to target RNA molecules. In particular, we focus on recognition between RNA and small-molecule binders, on selectivity, and on the expected properties of RNA ligands.